The diet myth : why the secret to health and weight loss is already in your gut - Spector, T. D. (Timothy David) (Overlook Press, 2015)
"From the author of Identically Different comes a new look at nutritional health, showing us that breakthrough research on microbiomes--the microbes in our stomachs--could hold the key to healthy, balanced diets,"--Novelist.